Voice and Accountability in Transfer Programs in Latin America and the Caribbean - Bain, Katherine; Braun, Franka; Saavedra, Jaime (World Bank, Washington, DC, 2012)
A two-day workshop, organized by the World Banks Poverty Reduction and Economic Management (PREM) and Human Development (HD) departments, was held in June 2005 in the Dominican Republic with the objective to explore whether voice and accountability can improve the effectiveness of Conditional Transfer Programs. Participants included government and civil society representatives from ten countries in the region, as well as World Bank staff. Among the recommendations, participants suggested applying clear and transparent targeting rules instead of secret formulas, locating interview sites in schools and health centers to reduce patronage and to allow for witnesses, using qualitative information to make targeting formulas fit local realities, allowing for verification of self-reported income information, defining targeting as a success when it achieves acceptance and comprehension of program goals, being clear about program rules, posting lists of beneficiaries in public places, using civil society organizations to facilitate the flow of information, improving incentives to encourage public service providers to provide better information and be more responsive, providing appeal mechanisms, and allowing beneficiaries to choose among competing providers.